Comparison of antioxidant capacities and cytotoxicities of certain fruit peels - Siriporn Okonogi (2018)
This work was undertaken to explore the potential of fruit waste materials as sources of powerful natural antioxidants. The peels of eight kinds of fruits commonly consumed and grown in Thailand were used. The ethanolic fruit peel extracts were subjected to the scavenging tests of DPPH and ABTS radicals. Results from both assays were in good agreement that the top three markedly high free radical-scavenging power was from the peel extracts of Punica granatum (pomegranate), Nephelium lappaceum (rambutan), and Garcinia mangostana (mangosteen). The IC50values to quench the DPPH free radicals of these three extracts were 0.003, 0.006, and 0.023 mg/ml and the trolox equivalent antioxidant capacity (TEAC) values from ABTS assay were 4.066, 3.074, and 3.001 mM/mg, respectively. The extract of mangosteen peel showed moderate toxicity to Caco-2 cells and high toxicity to peripheral blood mononuclear cells (PBMC) with the IC50values of 32.0 and 4.9 μg/ml, respectively. Pomegranate peel extract stimulated Caco-2 cell and PBMC proliferation with the ED50of 4.7 and 44.4 μg/ml, respectively. Peel extract of rambutan exhibited extremely high value of IC50(>100 μg/ml) against both cell types indicating non-toxic activity to the cells. It was concluded that the peel of rambutan may be considered potentially useful as a source of natural antioxidants for food or drug product because of its high antioxidant activity and non-toxic property to normal cells. © 2006 Elsevier Ltd. All rights reserved.